Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00167-015-3884-1
|View full text |Cite
|
Sign up to set email alerts
|

Infection recurrence factors in one- and two-stage total knee prosthesis exchanges

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 25 publications
1
44
0
2
Order By: Relevance
“…Of the sixteen included studies [8,11,12,13,14,15,16,17,18,19,21,22,23,24,25,26] that met the inclusion criteria, thirteen were retrospective studies [8,11,12,13,14,15,16,17,21,22,23,24,25]; nine were retrospective cohort studies [8,11,12,15,17,22,23,24,25], one was a retrospective case series [21], one was a retrospective descriptive study [16], one was a case-control study [13], and one was a large retrospective observational database study [14]. Three were prospective studies [18,19,26]; two prospective cohort studies [19,26], and one prospective observational cohort study [18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the sixteen included studies [8,11,12,13,14,15,16,17,18,19,21,22,23,24,25,26] that met the inclusion criteria, thirteen were retrospective studies [8,11,12,13,14,15,16,17,21,22,23,24,25]; nine were retrospective cohort studies [8,11,12,15,17,22,23,24,25], one was a retrospective case series [21], one was a retrospective descriptive study [16], one was a case-control study [13], and one was a large retrospective observational database study [14]. Three were prospective studies [18,19,26]; two prospective cohort studies [19,26], and one prospective observational cohort study [18].…”
Section: Resultsmentioning
confidence: 99%
“…Several surgical techniques are available for the management of established PJI in knee arthroplasty and these commonly include a single or two–stage revision. Controversy however exists regarding the use of single–stage revision surgery as some studies in the literature report a higher reinfection rate [3,8,11,12,13,14,15,16,17,18,27]. In this study, we systematically reviewed the available evidence regarding the effectiveness of single–stage revision in infected TKA with a focus on reinfection rate and functional outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of 1-stage exchange is that all arthroplasty materials are removed, decreasing the likelihood of persistent biofilm bacteria 60 . One study found that female patients who underwent 2-stage exchange arthroplasty with static spacers had an increased risk of reinfection compared with patients who underwent 1-stage exchange or 2-stage exchange with a dynamic spacer 61 . A systematic review comparing the 2 procedures demonstrated that 1-stage exchange arthroplasty had significantly lower reinfection rates in studies published after 2000, with higher functional outcomes 62 .…”
Section: Shoulder and Elbowmentioning
confidence: 99%
“…Tekrarlama riskini arttırmadan daha fazla konfor sunmak için, tek aşamalı değişim tercih edilebilir. [69] Dönen menteşeli implantların kullanıldığı, revizyonun sonuçlarının değerlendirildiği 10 yıllık bir seride, tek aşamalı değişim ile posterior kapsül ve kollateral bağların agresif debridmanı sonrası %93 oranında enfeksiyon kontrolü sağlanmıştır. [70] On iki çalışmanın derlendiği, 1200'den fazla eklemin tek aşamalı değişiminin en az beş yıllık takiplerinde, enfeksiyona rastlanmama oranı %83'tür.…”
Section: Ameli̇yat Süreci̇unclassified